The Role of Purinergic Receptors in Cancer-Induced Bone Pain - Sarah Falk; Maria Uldall; Anne-Marie Heegaard (Journal of Osteoporosis)
Cancer-induced bone pain severely compromises the quality of life of many patients suffering from bone metastasis, as current therapies leave some patients with inadequate pain relief. The recent development of specific animal models has increased the understanding of the molecular and cellular mechanisms underlying cancer-induced bone pain including the involvement of ATP and the purinergic receptors in the progression of the pain state. In nociception, ATP acts as an extracellular messenger to transmit sensory information both at the peripheral site of tissue damage and in the spinal cord. Several of the purinergic receptors have been shown to be important for the development and maintenance of neuropathic and inflammatory pain, and studies have demonstrated the importance of both peripheral and central mechanisms. We here provide an overview of the current literature on the role of purinergic receptors in cancer-induced bone pain with emphasis on some of the difficulties related to studying this complex pain state.